1992
DOI: 10.1099/00221287-138-6-1077
|View full text |Cite
|
Sign up to set email alerts
|

Ploidy of Bacillus subtilis exfusants: the haploid nature of cells forming colonies with biparental or prototrophic phenotypes

Abstract: To investigate the relationship between DNA content and cell volume, we have attempted to repeat the construction of stable BaciUus subtilis diploid cells through protoplast fusion. Colonies with a biparental phenotype and those with a prototrophic phenotype were identified among exfusants of a cross between two polyauxotrophic strains. The ploiay of cells constituting such colonies was assessed by protoplast self-fusion, determination of the DNA to dry weight ratio of exponentially growing cells, and by quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The other possibility is that the BsuM enzyme remained in the cytoplasmic portion of the donor R + M + cell in the fusant and that, upon division of the fusants, various quantities of the enzyme were distributed to the progeny cells depending on where the cell division took place. It has been demonstrated that L‐form colonies of B. subtilis arise among those of the bacillary form after PEG‐induced cell fusion (Hauser & Karamata, ), which indicates that cell division can occur while the fusant is still without the cell wall. As the L‐form B. subtilis cell divides by an extrusion–resolution mechanism that is independent of FtsZ (Leaver et al ., ), it is possible that a similar mechanism was involved in the division of the fused cells that were produced by random collision between the donor and the recipient protoplasts.…”
Section: Discussionmentioning
confidence: 99%
“…The other possibility is that the BsuM enzyme remained in the cytoplasmic portion of the donor R + M + cell in the fusant and that, upon division of the fusants, various quantities of the enzyme were distributed to the progeny cells depending on where the cell division took place. It has been demonstrated that L‐form colonies of B. subtilis arise among those of the bacillary form after PEG‐induced cell fusion (Hauser & Karamata, ), which indicates that cell division can occur while the fusant is still without the cell wall. As the L‐form B. subtilis cell divides by an extrusion–resolution mechanism that is independent of FtsZ (Leaver et al ., ), it is possible that a similar mechanism was involved in the division of the fused cells that were produced by random collision between the donor and the recipient protoplasts.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of any selective pressure, additional DNA is often lost, as if the cell tends to restore a normal D N hlvolume ratio, which apparently ensures the highest growth rate. For instance, it was recently shown that Bacilhs ~b t i l i s cells are unable to accommodate two complete chromosomes ; multiple chromosomal copies, present in fused protoplasts, are segregated in separate cells at the time of cell wall regeneration (Hauser & Karamata, 1992). Therefore, assuming that a cell tends to restore an optimal DNA/volume ratio, it is conceivable that diploidy of a given region could be compensated by deletion(s) in other, possibly non-essential, regions of the chromosome.…”
Section: Introductionmentioning
confidence: 99%